The Effect of an Educational Application on The Quality of Life and Treatment Adherence in Mothers of Children with Congenital Heart Disease Undergoing Cardiac Surgery: A Randomized Clinical Trial. - Rajabi, Mohammad Mehdi; Begjani, Jamalodin; Negarandeh, Reza (International Journal of Community Based Nursing & Midwifery, 2025)
Background: The primary caregivers of children with congenital heart disease (CHD) after cardiac surgery at home are often their mothers. Therefore, the quality of life (QoL) and treatment adherence (TA) of mothers are crucial for the prognosis of these children. This study evaluated the impact of a mobile educational application on the QoL and TA in mothers of children with CHD undergoing cardiac surgery. Methods: This randomized clinical trial was conducted on 72 mothers of children with CHD referred for cardiac surgery to Children's Medical Center Hospital, Tehran, Iran, from September 2023 to May 2024. Mothers were randomly assigned to intervention (n=36) and control (n=36) groups. The intervention group received the educational app upon discharge and used it for four weeks, while the control group received standard discharge education, which consisted of face-to-face education. Data were collected using a demographic form, the 36-Item Short Form Health Survey (SF-36), and the Modanloo Treatment Adherence Questionnaire at baseline and one month post-intervention. Data were analyzed using SPSS software version 26, with independent t-test, chi-square, and analysis of covariance. A significance level of P<0.05 was considered. Results: At baseline, no significant differences were observed between the two groups in total score of QoL (P=0.18) and TA (P=0.70). One month post-intervention, the intervention group showed significantly higher total scores in QoL (P<0.001) and TA (P<0.001) compared to the control group. Conclusion: Using mobile applications in home care education can significantly enhance the QoL and TA in mothers of children with CHD after surgery.